Changes of Serum Melatonin, Interleukin-6, Homocysteine, and Complement C3 and C4 Levels in Patients With Depression - Tao, Huai; Chen, Xia; Zhou, Hongfei; Fu, Jinhua; Yu, Qi; Liu, Yong (Frontiers in Psychology, 2020)
Objectives: Cytokines activation and low complement levels are common in depression patients.This study is aimed to investigate the clinical significance of changes in serum concentrations of melatonin (MT), interleukin-6 (IL-6), homocysteine (hcy), complement C3, and C4 in depression patients and relationships of them with depression activity. Methods: 95 depression patients, including first-episode group (n=43) and recurrent group (n=52), and 45 age- and gender-matched healthy controls (HC) were recruited. Serum levels of MT, IL-6, hcy, C3, and C4 in all samples were measured by using enzyme-linked immunosorbent assay(ELISA), chemiluminescence method, enzyme circulation method, immuno-scatter turbidimetric assay, respectively. Results: The serum MT, IL-6, and hcy levels in first-episode group (113.08±5.06 pg/ml, 2.06±0.12 g/L, and 13.87±0.45 μmol/L) and recurrent group (117.63±4.63 pg/ml, 2.20±0.12 pg/L, and 13.61±0.46 μmol/L) were significantly higher than those in control group (89.50±5.10 pg/ml, 1.57±0.06 g/L, 11.34±0.40 μmol/L). The serum levels of C3 in first-episode group (0.95±0.02 g/L) were significantly lower than those in recurrent group (1.05±0.03 g/L) and control group (1.12±0.03 g/L).There was no significant difference in serum C4 level between each group. Conclusions: These results suggest that higher serum MT, IL-6, and hcy levels were correlated with pathogenesis of depression.